Cluster kinematics and stellar rotation in NGC 419 with MUSE and adaptive optics. Issue 2 (24th July 2018) - Kamann, S; Bastian, N; Husser, T-O; Martocchia, S; Usher, C; den Brok, M; Dreizler, S; Kelz, A; Krajnović, D; Richard, J; Steinmetz, M; Weilbacher, P M
ABSTRACT: We present adaptive optics (AO)-assisted integral-field spectroscopy of the intermediate-age star cluster NGC 419 in the Small Magellanic Cloud. By investigating the cluster dynamics and the rotation properties of main-sequence turn-off (MSTO) stars, we demonstrate the power of AO-fed MUSE observations for this class of objects. Based on $1\, 049$ radial velocity measurements, we determine a dynamical cluster mass of $1.4± 0.2× 10^5\, {\rm M_\odot}$ and a dynamical mass-to-light ratio of 0.67 ± 0.08, marginally higher than simple stellar population predictions for a Kroupa initial mass function. A stacking analysis of spectra at both sides of the extended MSTO reveals significant rotational broadening. Our analysis further provides tentative evidence that red MSTO stars rotate faster than their blue counterparts. We find average V sin i values of $87± 16$ and $130± 22\, {\rm km\, s^{-1}}$ for blue and red MSTO stars, respectively. Potential systematic effects due to the low-spectral resolution of MUSE can reach $30\, {\rm km\, s^{-1}}$ but the difference in V sin i between the populations is unlikely to be affected.